PENGENDALIAN ROBOT YANG MEMILIKI LIMA DERAJAT KEBEBASAN - Deny Wiria Nugraha (Foristek, 2011)
This study design controls a robotic arm is a robotic transfer of goods which have five degrees of freedom by using a system of point-topoint programming, the robot is quite necessary in the industrial world today, because it can be programmed back so that makes the robot to be flexible in working out various things. The design of this arm robot control system using the computer as a data processor with PPI-8255 interface and parallel port (LPT1). Robot software system designed to control the robot to do a certain task is instructed via keybord. Control of motor rotation in the robot is done through software on personal computers and the robot is designed to be controlled manually or automatically using the program Delphi 7.0.